2020
DOI: 10.1155/2020/6287274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Primary Posterior Continuous Curvilinear Capsulorhexis in Postvitrectomy Cataract Eyes

Abstract: Purpose. To evaluate the safety and outcomes of primary posterior continuous curvilinear capsulorhexis (PPCCC) combined with phacoemulsification in postvitrectomy eyes. Design. Retrospective case series. Methods. Twenty-one postvitrectomy eyes of 21 patients with cataract between April 2017 and December 2019 were enrolled. PPCCC through the cornea incision was performed before in-the-bag intraocular lens implantation. All patients were followed up for at least 3 months postoperatively. The outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In our study, 29 of 54 patients [23]. As a result of the high incidence of PCO in patients with previous PPV surgery, previous study has proposed that PCCC combined with phacoemulsification may be an alternative to prevent PCO in postvitrectomy eyes with cataract [24]. Previous studies have found capsulorhexis size and its central localization play important roles in PCO [25,26].…”
Section: Classification Of Capsulorhexis Overlap Iol Edgesmentioning
confidence: 55%
See 1 more Smart Citation
“…In our study, 29 of 54 patients [23]. As a result of the high incidence of PCO in patients with previous PPV surgery, previous study has proposed that PCCC combined with phacoemulsification may be an alternative to prevent PCO in postvitrectomy eyes with cataract [24]. Previous studies have found capsulorhexis size and its central localization play important roles in PCO [25,26].…”
Section: Classification Of Capsulorhexis Overlap Iol Edgesmentioning
confidence: 55%
“…Additionally, loss of support of the vitreous body may affect the attachment between IOL edge and capsular bag, promoting rapid LEC proliferation and contributing to PCO [ 23 ]. As a result of the high incidence of PCO in patients with previous PPV surgery, previous study has proposed that PCCC combined with phacoemulsification may be an alternative to prevent PCO in postvitrectomy eyes with cataract [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, PPCCC is widely used in paediatric cataract surgery in the hope of preventing PCO, but not routinely adopted in adult cataract surgery, attributing to concerns regarding associated complications, including vitreous interface damage, vitreous prolapse, resulting cystoid macular oedema, and even retinal detachment. Published studies have demonstrated the safety and efficacy of PPCCC in age-related cataract [ 34 36 ]. In our study, PPCCC had no effect on the patient's subjective perception.…”
Section: Discussionmentioning
confidence: 99%